2017
DOI: 10.1103/physrevlett.118.222301
|View full text |Cite
|
Sign up to set email alerts
|

Azimuthally Differential Pion Femtoscopy in Pb-Pb Collisions at sNN=2.76TeV

Abstract: We present the first azimuthally differential measurements of the pion source size relative to the second harmonic event plane in Pb-Pb collisions at a center-of-mass energy per nucleon-nucleon pair of ffiffiffiffiffiffiffiffi s NN p ¼ 2.76 TeV. The measurements have been performed in the centrality range 0%-50% and for pion pair transverse momenta 0.2 < k T < 0.7 GeV=c. We find that the R side and R out radii, which characterize the pion source size in the directions perpendicular and parallel to the pion tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 90 publications
1
5
0
Order By: Relevance
“…One can see, however, that the relative magnitude of the radii oscillations is reproduced fairly well. For instance, ∆R 2 out and ∆R 2 side between the maxima and minima values do not exceed 15-20% for second-order oscillations [13] and 8-12% for third-order ones [14]. HYDJET++ calculations nicely match these results.…”
Section: Results Of the Simultaneous Description Ofsupporting
confidence: 55%
See 2 more Smart Citations
“…One can see, however, that the relative magnitude of the radii oscillations is reproduced fairly well. For instance, ∆R 2 out and ∆R 2 side between the maxima and minima values do not exceed 15-20% for second-order oscillations [13] and 8-12% for third-order ones [14]. HYDJET++ calculations nicely match these results.…”
Section: Results Of the Simultaneous Description Ofsupporting
confidence: 55%
“…The calculations with ε 2 = ±0.3 are displayed in Figure 1. ALICE data from [13] for the momentum interval 0.5 < k T < 0.7 GeV/c are plotted onto the calculations also. Recall that the main goal of our present study is the search for the influence of pure spatial and pure dynamical anisotropies on the harmonics of anisotropic flow and femtoscopic radii.…”
Section: Results Of the Simultaneous Description Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…ported by the ALICE Collaboration have shown that, when taking the difference between the yields per trigger particle in high-multiplicity and low-multiplicity events, two nearly identical long-range ridge-like excess structures on the near-side and away-side, the so-called "double ridge", arise [9,10]. Results on two-particle correlations of identified hadrons [11][12][13][14] and of Bose-Einstein (HBT) correlations [15,16] further stressed the initial observations, showing striking similarities between pp, p-Pb and Pb-Pb collisions, consistent with the hydrodynamic picture of a particle-production source expanding more explosively along the collision event plane.…”
Section: Collective Phenomenamentioning
confidence: 99%
“…Improvements can be associated with the UA effects in skeletal muscle [241]. Many studies were indicated that the improved making of irisin in the muscle induced through physical exercise could encourage the making of neurotrophins in the hippocampus [242], neurogenesis, and synaptogenesis in rodents [243]. Multiple synthesized methods based on UA with anti-diabetic, anti-inflammatory, and cardioprotective were identified [243], the neuroprotective potential of UA and analogous compounds, advising, which they can be helpful to the management of PD and AD.…”
Section: Clinical Trialsmentioning
confidence: 99%